ANALYSIS OF THE DEMAND FUNCTION FOR ELECTRIC POWER IN DIWANIYAH GOVERNORATE - Haider Kadhim Mahdi (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
Electric energy is one of the important and basic elements of economic activity as well as other life activities, so the research was concerned with one of the important elements involved in generating gross domestic product (GDP), the research problem centers on the difficulties and obstacles that the electricity sector in Iraq faces, despite the continuous rise in energy production However, there is a large gap between the supply and demand for that energy, resulting from the large increase in the volume of losses due to the weakness of the transmission lines of electrical energy. And the frequent excesses by citizens. Carrying out a comprehensive campaign for the maintenance and maintenance of electric transmission networks and lifting the excesses can contribute to reducing the volume of waste and increasing the volume of supply and thus raising the processing hours for the units consuming electrical energy.